Pendekatan strategi dalam produk digital dan risiko: Studi literatur pada transformasi pemasaran bank syariah dan fintech - Ambiya, Ahmad Zhafa (Maliki Interdisciplinary Journal, 2025)
Digital transformation has impacted marketing and product development in Islamic financial institutions and Sharia-compliant fintechs. A literature review of three articles in the Maliki Islamic Journal shows that successful strategic approaches include customer-centric strategies, platform partnerships, and agile product development, based on the principle of compliance-by-design. This approach enables Islamic financial institutions to innovate through digital services such as mobile banking, halal e-wallets, and platform-based financing, while maintaining Sharia values. However, this innovation also presents new challenges, including cyber risk, digital operational risk, Sharia compliance, reputational risk, and a shortage of competent talent. Therefore, integrated risk management is needed through the implementation of enterprise risk management, digital Sharia audits, and human resource development in the Sharia-tech sector. Collaboration between banks, fintechs, and regulatory bodies such as the Financial Services Authority (OJK) and the National Sharia Council (DSN-MUI) is crucial in ensuring the sustainability of and public trust in the digital Islamic financial system.